Green Infrastructure 2021
DOI: 10.1007/978-981-16-6383-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Bending and Rolling Shear Properties of Cross-Laminated Timber (CLT) as Engineered Sustainable Construction Materials

Abstract: Cross-laminated timber (CLT) is one of the preferred engineered timber products (ETP) used in the construction and building industry. CLT is an orthogonal and laminar structure that can be used as full-size load-bearing structural elements such as wall, floor element as well as a linear timber member. The timber pieces are visually graded before being manufactured into CLT panels. As a result, CLT is able to provide enhanced stability and performance compared with its solid timber counterparts. In order to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The mechanical properties of hybrid (mixed-species) cross-laminated timber (CLT) panels made with low-value sugar maple (Acer saccharum) surface layers and white spruce (Picea glauca) were improved significantly compared with those of the current standard layups (Ma et al 2021). Lum et al (2022) provided an overview of the bending and shear properties of CLT made from different timber species with various densities including timbers such as softwood, temperate hardwood as well as tropical hardwood. Validation of relatively simple FEM models for simulation and virtual prototyping of alternative CLT combinations also revealed that for shear tests, the lack of orthotropic material properties of hybrid poplar could be sufficiently substituted by using cottonwood (Populus delotides) material properties (Sebera et al 2015).…”
Section: Mixedhybrid Cltmentioning
confidence: 99%
“…The mechanical properties of hybrid (mixed-species) cross-laminated timber (CLT) panels made with low-value sugar maple (Acer saccharum) surface layers and white spruce (Picea glauca) were improved significantly compared with those of the current standard layups (Ma et al 2021). Lum et al (2022) provided an overview of the bending and shear properties of CLT made from different timber species with various densities including timbers such as softwood, temperate hardwood as well as tropical hardwood. Validation of relatively simple FEM models for simulation and virtual prototyping of alternative CLT combinations also revealed that for shear tests, the lack of orthotropic material properties of hybrid poplar could be sufficiently substituted by using cottonwood (Populus delotides) material properties (Sebera et al 2015).…”
Section: Mixedhybrid Cltmentioning
confidence: 99%